Application of piezoelectric materials in the field of bone: a bibliometric analysis - Zhang, Yu-Qin; Geng, Qian; Li, Chao; Wang, Hai-Cheng; Ren, Chuan; Zhang, Yi-Fan; Bai, Jun-Sheng; Pan, Hao-Bo; Cui, Xu; Yao, Meng-Xuan; Chen, Wei (Frontiers in Bioengineering and Biotechnology, 2023)
In the past four decades, many articles have reported on the effects of the piezoelectric effect on bone formation and the research progress of piezoelectric biomaterials in orthopedics. The purpose of this study is to comprehensively evaluate all existing research and latest developments in the field of bone piezoelectricity, and to explore potential research directions in this area. To assess the overall trend in this field over the past 40 years, this study comprehensively collected literature reviews in this field using a literature retrieval program, applied bibliometric methods and visual analysis using CiteSpace and R language, and identified and investigated publications based on publication year (1984-2022), type of literature, language, country, institution, author, journal, keywords, and citation counts. The results show that the most productive countries in this field are China, the United States, and Italy. The journal with the most publications in the field of bone piezoelectricity is the International Journal of Oral & Maxillofacial Implants, followed by Implant Dentistry. The most productive authors are Lanceros-Méndez S, followed by Sohn D.S. Further research on the results obtained leads to the conclusion that the research direction of this field mainly includes piezoelectric surgery, piezoelectric bone tissue engineering scaffold, manufacturing artificial cochleae for hearing loss patients, among which the piezoelectric bone tissue engineering scaffold is the main research direction in this field. The piezoelectric materials involved in this direction mainly include PHBV, PVDF, and BaTiO3.